Motion improvised miniaturized dual focus lens module based on piezoelectric actuator for the medical applications. Issue 1 (3rd October 2022) - Bhokare, Saurabh Gajanan; Behera, Basudeba
Abstract: In this work, we have designed a miniaturized dual focus module using a piezo-electric actuator for application in mobile. The device mainly consists of two lens mounts for holding the Alvarez-Lohmann lens. One of the lens mounts is stationary while another is rotated with the help of a piezoelectric actuator. The materials used for the development of the device are combinations of aluminum for chassis and lead zirconate titanate as piezo material for actuator. The movement of the actuator tip is an elliptical shape which used to facilitate the force to the lens. Mainly the mathematical modeling and finite element simulation of the device are carried out using COMSOL Multiphysics. The actuator rotates the mounted lens for 0.12 ° in one elliptical cycle at the applied voltage of 100 V with the resonance frequency. The device has a scope of applications in medical equipment such as a 3 D camera which is required mainly for disease diagnosis and medical operation purposes.